The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Composite Materials: Fatigue and Fracture: Fifth Volume 1995
DOI: 10.1520/stp14009s
|View full text |Cite
|
Sign up to set email alerts
|

Mode III Delamination Using a Split Cantilever Beam

Abstract: In this study, 48-ply AS4/3501-6 (carbon fiber reinforced epoxy) laminates were delaminated in essentially pure Mode III using a modified split cantilever beam (SCB) Mode III test. For this test, two loads are applied directly to each arm of a SCB specimen using a pair of identical grips. The complex loading configuration is necessary to reduce the Mode II loading which is dominant at the free edges when a single load is applied to each arm. Finite element analysis of a three-dimensional mesh confirmed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…[126]. Two forces are applied directly to each crack arm of the SCB specimen, as illustrated in Fig.…”
Section: Fracture Studiesmentioning
confidence: 99%
“…[126]. Two forces are applied directly to each crack arm of the SCB specimen, as illustrated in Fig.…”
Section: Fracture Studiesmentioning
confidence: 99%
“…Robinson and Song [6] tried to limit the bending moment by introducing additional constraints, but they concluded that the experimental Compliance Calibration (CC) method could no longer be applied in the data reduction schema. Another modified version of SCB configuration (MSCB) was then realized by Sharif et al [7], whose specimen was loaded by special grips and the mode II component was significantly reduced. The data reduction method based on an improved beam theory was found to be more reliable than the CC method [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, Martin [22] has shown that a significant amount of mode II is present in this specimen. Modified versions of the SCB test are able to eliminate some of the mode II component [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the object of this study is to investigate the mode III fracture properties of glass fiber reinforced polymer woven laminates at low temperatures. For this purpose, a modification of the SCB specimen is used as proposed in [24]. A special loading rig is implemented in order to eliminate the bending moment at the delamination front.…”
Section: Introductionmentioning
confidence: 99%